The relationship between atrial myopathy with and without atrial fibrillation to cryptogenic stroke - Kahadi, Cik; Rizal , Ardian; Rohman, Mohammad Saifur (Universitas Brawijaya, 2025)
Background: Ischemic stroke is the second most common cause of mortality globally, with some cases classified as cryptogenic strokes (CS) where the cause is unknown. Traditionally, atrial fibrillation (AF) has been considered the primary cause of ischemic stroke, but recent clinical trials and the occurrence of CS have led to the concept of atrial myopathy (AM). AM not only serves as a substrate for AF, promoting thrombus formation, but also causes blood stasis in the atrium, resulting in stroke without AF. Objective: The relationship between AM with and without AF to CS incidences at Saiful Anwar Hospital, Malang was evaluated in this study. Methods: Retrospectively analyzed medical records of patients from January 2023 to December 2024. Univariate analysis for baseline characteristic, bivariate analysis with Chi square, t-test and Mann Whitney u-test and multivariate analysis for predictive model using logistic regression were used for determine the relationship among variable in this study. Result: 112 patients were included in this study. AM has a statistically significant (OR 31.762, 95% CI: 3.965-254.427, p=0.001) as a predictor of CS, but AF did not (OR: 1.666, 95% CI: 0.414-6.707, p=0.473). A better predictive value was achieved with CHA2DS2-VASC ≥2 combined with AM (OR 7.948, 95% CI: 2.628-24.034, p<0.001), compared with CHA2DS2-VASC ≥2 alone (OR 1.909, 95% CI: 0.651-5.598, p=0.239) or CHA2DS2-VASC ≥2 combined with AF and AM (OR 3.600, 95% CI: 0.985-13.159, p=0.050). Conclusion: Atrial myopathy with and without atrial fibrillation had association to increasing the risk of cryptogenic stroke. Combining AM with the CHA2DS2-VASC score can improve stroke cryptogenic risk prediction